PERUBAHAN INTERAKSIONAL MASYARAKAT ( Studi Kasus Desa Wisata Plosokuning Desa Bangunkerto Kecamatan Turi Kabupaten Sleman) - Icha Novita Br. Sembiring; Eko Murdiyanto; Budi Widayanto (Agrisociabus, 2022)
This research aims to 1 Examine the process of interactional change on community of Plosokuning Tourism Village 2 Examine the forms of interactional on community of Plosokuning Tourism Village. This research uses a qualitative method with a case of study approach. Determinantion of data sources was done purposive namely chairman of Plosokuning Tourism Village, the community of Plosokuning, and the staff of Plosokuning Tourism Villlage. The data used in this study are primary data and secondar data. Data collection tehcniques with observation, interviews and documentation by testing validity of data using triangulation sources. Data analysis technique with collecting data, data reduction, data presentation, and withdrawal of conclusion and verification. The result of the research are 1 the interactional changes that occur in the Plosokuning Tourism Village can be seen from the social contact and social communication that occur between the community of Plosokuning 2 The interactional changes that occur in the Plosokuning Tourism Village are associative changes. Keywords: Community, Interactional, Plosokuning Village